FC 039RENAL OUTCOME AFTER RITUXIMAB IN ADULT-ONSET IGA VASCULITIS AND CRESCENTIC IGA NEPHROPATHY: A MULTICENTRE STUDY. (29th May 2021) - Trivioli, Giorgio; Canzian, Alice; Maritati, Federica; Fenoglio, Roberta; Pillebout, Evangeline; Urban, Maria Letizia; Mohammad, Aladdin; Nogueira, Estela; Silvestri, Elena; Eriksson, Per; Segelmark, Mårten; Novikov, Pavel; et al.
Abstract: Background and Aims: Glucocorticoids (GC) and/or immunosuppressive agents are the mainstay of therapy for adult-onset IgA Vasculitis (IgAV), but their efficacy is often partial while their toxicity is relevant. Recently, rituximab (RTX) has been reported as a safe and effective option but only few data on renal outcome are available. 1 RTX has also been used in a few cases of crescentic IgA Nephropathy (cIgAN), an IgAN subset with vasculitic lesions and poor response to conventional immunosuppressive regimens. 2 We present the results of a multicentre cohort of patients with IgAV and cIgAN treated with RTX. Method: The databases of 16 consorted European centres were investigated to screen for patients with adult-onset, biopsy-proven IgAV and cIgAN (crescents in ≥25% glomeruli and rapid eGFR worsening at presentation), who received RTX as induction therapy. We selected patients with active renal manifestations at the time of RTX. Remission was defined as a Birmingham Vasculitis Activity Score (BVAS)=0 or <5 if it was due to persistent proteinuria and relapse as an increase in BVAS requiring change in immunosuppressive therapy. Results: We identified 38 patients with IgAV and 12 patients with cIgAN who received RTX and had active renal involvement at the time of treatment. The median age at onset was 40 years (interquartile range, IQR, 25-53) and more than two-thirds of patients were male ( Table 1 ). The median follow-up after RTX was 41 months (IQR 18-60). Renal outcomes are reported in Table 2 . At the time of treatment, 24 patients (48%) had eGFR ≥60 mL/min/1.73 m 2 . All had IgAV and their median BVAS was 17 (IQR 10-22). Furthermore, all had microhaematuria and proteinuria. Renal histology showed mesangial or focal endocapillary proliferation in 12/17 (71%) patients who underwent biopsy (class II-IIIA according to Pillebout 3 ). Twenty patients (83%) achieved remission; after a median of 12 months (range 9-14), four experienced a minor relapse and one had a major relapse with significant renal disease progression. Renal function remained stable in all but two patients who developed end-stage renal disease (ESRD). Micro-haematuria subsided in 14/24 (58%) and median 24h proteinuria decreased from 1750 mg (IQR 865-3275) to 175 mg (IQR 100-800) at last follow-up (p=0.029). Of the 26 patients with eGFR <60 mL/min/1.73 m 2, 14 had IgAV and 12 had cIgAN. All were biopsied and 20 (77%) had diffuse endo/extra-capillary proliferation (classes IIIB-IV). Five patients required dialysis but recovered soon after treatment start. Remission was achieved by 16/26 (61%); eight (50%) subsequently relapsed and two (12%) reached ESRD. At last follow-up, eGFR was ≥60 mL/min/1.73 m 2 in 8/26 (31%), 10/26 (48%) had stable renal function as compared to the time of RTX, while 8/26 (31%) had developed ESRD. Median 24h proteinuria decreased from 3400 mg (IQR 2150-6500) to 770 mg (177-1315) (p=0.016). Remission rate and ESRD-free survival were respectively 86% and 92% in patients with IgAV, while they were respectively 42% and 42% in cIgAN patients. Furthermore, 21/24 (87%) patients who received RTX alone or combined to glucocorticoids but not to immunosuppressive agents achieved remission and 22/24 (92%) were ESRD-free at last follow-up. Of the 26 patients receiving immunosuppressive agents, 17 (65%) obtained remission and 18 (69%) were ESRD-free at last assessment. Over the whole follow-up, only one patient reported a severe adverse effect related to RTX (pneumonia). Conclusion: Renal involvement in adult-onset IgAV and cIgAN is frequently severe. RTX, combined or not with other immunosuppressive agents, may improve renal manifestations and is well tolerated. IgAV patients show higher remission rates and a longer ESRD-free survival as compared to cIgAN patients.